2014
DOI: 10.5588/pha.13.0111
|View full text |Cite
|
Sign up to set email alerts
|

Management of previously treated tuberculosis patients in Kalutara district, Sri Lanka: how are we faring?

Abstract: Of all retreatment patients, only 79% were tested for CDST and there were sizeable delays in sample transportation and treatment initiation. Possible ways forward to strengthen the programme are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…This indicates a huge gap in diagnosis of MDR-TB: India, Indonesia and Nigeria alone accounting for almost half of the gap. Studies worldwide have raised concerns over high attrition and/or delays in MDR-TB DTP [2–8]. …”
Section: Introductionmentioning
confidence: 99%
“…This indicates a huge gap in diagnosis of MDR-TB: India, Indonesia and Nigeria alone accounting for almost half of the gap. Studies worldwide have raised concerns over high attrition and/or delays in MDR-TB DTP [2–8]. …”
Section: Introductionmentioning
confidence: 99%
“…15 A study from Sri Lanka had led to the creation of a mid-level programme officer post at subdistrict level. 16 Change in hospital-level policy/practice There were several instances of change in policy at the level of the hospital or institution. A study from China had led to the prolongation of the treatment of TB patients with co-existing diabetes mellitus in their hospital.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Only about half of the patients were tested in our study, compared to 10% in Tanzania, 9 39% in China, 5 40% in Malawi, 7 50% in Cambodia, 4 64% in Andhra Pradesh, India, 9 74% in Delhi, India 10 and 79% in Sri Lanka. 8 All the above studies took place in settings that used phenotypic diagnostic techniques. Variations worldwide could be due to differences in the criteria for presumptive MDR-TB or in the settings and phase of PMDT implementation.…”
Section: Discussionmentioning
confidence: 99%
“…2 Studies from around the world have raised concerns over the high pre-diagnostic and pre-treatment attrition in MDR-TB diagnosis and treatment pathways (DTP). [3][4][5][6][7][8][9] Most of these studies were conducted in settings with the capacity for phenotypic diagnostic techniques, with a long turnaround time (TAT). A study from New Delhi, India, identified a significant decrease in TAT and pre-treatment loss to follow-up in 2014 after the introduction of line probe assay (LPA) technology, mainly attributed to a decrease in laboratory diagnostic time, although other operational issues were still of concern.…”
mentioning
confidence: 99%